2023
DOI: 10.36253/qoe-14603
|View full text |Cite
|
Sign up to set email alerts
|

Do parties adjust their policy proposals to the political context? A study of election promises during the 2022 Italian general election

Abstract: This paper investigates towards which policy issues Italian political parties oriented their commitments in the run-up to the 2022 parliamentary election. Do parties make more promises in salient domains? Or, do they prioritise those issues in which they enjoy ownership? To answer these questions, we created a novel dataset that contains 3,992 election pledges made by Italian political parties in the 2022 electoral campaign. By looking at the programmatic policies included in the campaign manifestos of the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Surprisingly, data show no significant effect when posts refer to other topics that have been at the center of the political discussion throughout the campaign (e.g., health issues, environment, international policy). This finding, however, is in line with Borgnino and Palma (2023), who found that parties did not significantly adjust their election pledges on such issues.…”
Section: Discussionsupporting
confidence: 85%
“…Surprisingly, data show no significant effect when posts refer to other topics that have been at the center of the political discussion throughout the campaign (e.g., health issues, environment, international policy). This finding, however, is in line with Borgnino and Palma (2023), who found that parties did not significantly adjust their election pledges on such issues.…”
Section: Discussionsupporting
confidence: 85%